2020
DOI: 10.1002/jtr.2361
|View full text |Cite
|
Sign up to set email alerts
|

Identifying active resident hosts of VFR visitors

Abstract: Substantial tourism activity can be attributed to visiting friends and relatives travel. However, the identification and classification of hosts who are most active, participating in touristic attractions and culture, has received limited attention. This study surveyed residents of Toronto, Canada, and segmented them depending on their own activity while hosting. Findings show that highly active hosts are more likely to be immigrants, to be entertaining large groups of both friends and relatives, and to be hos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 57 publications
(98 reference statements)
1
22
0
Order By: Relevance
“…This research aimed at investigating the difference for students between hosting friends versus relatives, how they experience and perceive their own role as hosts and how they plan activities with their guests. In line with Griffin and Guttentag (2020), our results show that SHFR is a multidimensional phenomenon, characterized by the type of guests, the hosting style, high levels of both outdoor and indoor host involvement and seasonality (due to the summer break).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This research aimed at investigating the difference for students between hosting friends versus relatives, how they experience and perceive their own role as hosts and how they plan activities with their guests. In line with Griffin and Guttentag (2020), our results show that SHFR is a multidimensional phenomenon, characterized by the type of guests, the hosting style, high levels of both outdoor and indoor host involvement and seasonality (due to the summer break).…”
Section: Discussionsupporting
confidence: 87%
“…The qualitative study addresses RQ2 by elaborating on the findings of the quantitative study and seeks to understand the role and experiences of students as hosts. We thereby address the call for an empirical understanding of different hosting styles (Griffin and Guttentag, 2020) and of social relations embodied in hosting practices (Janta and Christou, 2019). Data were collected in Innsbruck (Austria), a major alpine university town in Europe, with a resident population of 132,000 plus 27,000 university students, including about 13,000 international students (Universita ¨t Innsbruck, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The functional role of international students can be distinctive based on their unique network, activities and knowledge constructed upon their own learning during the period of education. Such active participation may be easier than encouraging local residents in contributing to tourism development and community-based complexity in cities (Griffin and Guttentag, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These researchers called for a comparative analysis of hosts from different origins for both theoretical, management and marketing implications. Griffin and Glover (2020) and Griffin and Guttentag (2020) revealed that hosting VFR visitors creates an experiential and relational context of personal refreshment, resource exchange and capital generation that enhance hosts’ habitus. Hosts would have a changing impact on their personal identity, sense of accomplishments, level of familiarity with the new culture and destinations that may contribute to further integration.…”
Section: Literature Reviewmentioning
confidence: 99%